Autonomy support beyond the language learning classroom : a self-determination theory perspective - Mynard, Jo; Shelton-Strong, Scott J., 1966- (Bristol ; Jackson : Multilingual Matters, 2022)
"Through the application of self-determination theory (SDT) to research and practice, this book deepens our understanding of how autonomous language learning can be supported and understood outside of the classroom. The chapters deal with learning environments and open spaces, communities and relationships, and advising and self-access"--
Introduction : autonomy support beyond the language learning classroom : a self-determination theory perspective / Jo Mynard and Scott J. Shelton-Strong -- Part 1: Theoretical underpinnings. A brief but comprehensive overview of self-determination theory / Johnmarshall Reeve -- What it means 'to take ownership over one's own learning' in a self-determination theory analysis / Johnmarshall Reeve -- Part 2: Autonomy support in learning environments and open spaces. Understanding inner motivational resources of language learners' out-of-class technology use for language learning / Ali Dincer and Tuba Işık -- Vietnamese EFL students' out-of-classroom motivation viewed through self-determination theory / Xuan Hoang, Alice Chik, Ruth French, and Sue Ollerhead -- Autonomy-supportive online EFL writing : a self-determination theory perspective / Yanling Li, Jiaxiu Zhang and Pingying Hu -- Creating social learning opportunities outside the classroom : how interest-based learning communities support learners' basic psychological needs / Satoko Watkins -- Part 3: Autonomy support in communities and relationships. Self-determined motivation in language learning beyond the classroom : interpersonal, intergroup and intercultural processes / Mustafa Firat, Kimberly A. Noels, Nigel Mantou Lou -- The quality of our connections matters : relationships motivation theory in independent language learning / W.L. Quint Oga-Baldwin -- Establishing high-quality relationships through a mentoring programme : relationships motivation theory / Satoko Kato -- Part 4: Autonomy support in advising and self-access for language learning. Facilitating an autonomy-supportive learning climate : advising in language learning and basic psychological needs / Scott J. Shelton-Strong, María Giovanna Tassinari -- Mindfulness and advising in language learning : a self-determination theory perspective / Micòl Beseghi -- Reimagining the self-access centre as a place to thrive / Jo Mynard -- Conclusion : where to go from here? / Scott J. Shelton-Strong.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Print version record.
JSTOR
Keywords: Second language acquisition -- Psychological aspects; Language and languages -- Study and teaching -- Psychological aspects; Autonomy (Psychology); Motivation in education; Informal language learning; Non-formal education; Second language acquisition; Langue seconde -- Acquisition -- Aspect psychologique; Langue seconde -- Acquisition; Motivation en éducation.; Apprentissage informel des langues; Éducation non formelle; PSYCHOLOGY -- General; Autonomy (Psychology); Informal language learning; Language and languages -- Study and teaching -- Psychological aspects; Motivation in education; Non-formal education; Second language acquisition -- Psychological aspects; PSYCHOLOGY / General; Essay; essays; Essays; Essays; Essais